2018
DOI: 10.1038/s41598-018-25019-1
|View full text |Cite
|
Sign up to set email alerts
|

A Temporal Examination of Platelet Counts as a Predictor of Prognosis in Lung, Prostate, and Colon Cancer Patients

Abstract: Platelets, components of hemostasis, when present in excess (>400 K/μL, thrombocytosis) have also been associated with worse outcomes in lung, ovarian, breast, renal, and colorectal cancer patients. Associations between thrombocytosis and cancer outcomes have been made mostly from single-time-point studies, often at the time of diagnosis. Using laboratory data from the Department of Veterans Affairs (VA), we examined the potential benefits of using longitudinal platelet counts in improving patient prognosis pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 37 publications
3
26
0
Order By: Relevance
“…Prior studies have reported associations between C‐reactive protein 26 and the erythrocyte sedimentation rate 27 and mortality in patients with localized prostate cancer. These LWAS findings have confirmed prior reports demonstrating that markers of the systemic inflammatory response are associated with mortality among patients diagnosed with cancer 28,29 . To the best of our knowledge, the question of whether these findings more broadly reflect the overall health of a patient, the systemic effects of cancer before a formal diagnosis of prostate cancer, or a susceptibility to cancer progression is unknown.…”
Section: Discussionsupporting
confidence: 85%
“…Prior studies have reported associations between C‐reactive protein 26 and the erythrocyte sedimentation rate 27 and mortality in patients with localized prostate cancer. These LWAS findings have confirmed prior reports demonstrating that markers of the systemic inflammatory response are associated with mortality among patients diagnosed with cancer 28,29 . To the best of our knowledge, the question of whether these findings more broadly reflect the overall health of a patient, the systemic effects of cancer before a formal diagnosis of prostate cancer, or a susceptibility to cancer progression is unknown.…”
Section: Discussionsupporting
confidence: 85%
“…Several types of cancer, especially gastric, colorectal, pancreatic, prostate, lung, and esophageal squamous cell carcinomas, have been associated with elevated plasma fibrinogen levels and PLT counts [2,[8][9][10]. The current study findings showed that patients with negative lymph nodes have significantly lower PLT counts and fibrinogen levels than patients with positive lymph nodes.…”
Section: Discussionsupporting
confidence: 48%
“…It is also not known whether selective silencing of hepatic THPO would also reduce platelet count or improve outcomes in cancer-associated thrombocytosis in humans, observed in 15% to 40% of solid tumor patients. 52 In a thorough pioneering study, Stone and colleagues have documented reduction of experimental paraneoplastic thrombocytosis and associated antineoplastic effects using a TPO small interfering RNA, with or without also inhibiting interleukin-6. 3 This indicated that paraneoplastic thrombocytosis is responsive to THPO gene silencing in some mouse models.…”
Section: Discussionmentioning
confidence: 99%